TRANSFORMASI HUBUNGAN KIAI DAN SANTRI DALAM KONTEKS PERUBAHAN SOSIAL KONTEMPORER - Jati Pamungkas (Institut Agama Islam Ngawi, 2023)
Islamic boarding schools (pesantren) are the oldest Islamic educational institutions in Indonesia, having maintained a distinctive pattern of relationships between kiai (Islamic scholars) and santri (students) for centuries. This relationship is not merely educational in nature but also encompasses spiritual, cultural, and social dimensions. However, the advancement of modernization, globalization, digitalization, and increasing access to formal education has brought significant changes to interaction patterns within pesantren communities. This article aims to analyze the transformation of kiai–santri relations within the context of contemporary social change. The study employs a descriptive qualitative approach using a literature review method through the analysis of various scholarly works on pesantren, social change, and religious authority relations. The findings reveal that the relationship between kiai and santri has shifted from a highly hierarchical patron–client model toward a more dialogical and participatory form. Nevertheless, the moral and spiritual authority of the kiai remains a central element in pesantren life. These transformations are influenced by the development of information technology, the modernization of educational systems, the increasing literacy and critical awareness of santri, and broader changes in social structures. The study demonstrates that pesantren have been able to adapt to social changes while preserving their Islamic identity and traditions, which continue to serve as the foundation of their existence.